Identification and analysis of drivers affecting the maturity of knowledge management in Tehran Municipal Sports Organization - ismail khandan; Ali Mohammad Safania; Mohsen Baghrian Farahabadi; Seyyed Salahuddin i Naqshband (مدیریت و چشم انداز آموزش)
AbstractThe aim of the current research is to design a model of the drivers that influence the maturity of knowledge management in the sports organization of Tehran Municipality. According to its purpose, the research method is applicable; qualitative in terms of implementation; and analytical and exploratory in nature. The statistical population includes 19 experts and faculty members of universities selected by the purposeful sampling method. Data collection was done using semi-structured interviews with members of the statistical community. The analysis of the data was done by the metacombination method, and MICMAC software was used. The data analysis showed that 32 key indicators and 9 sectors were identified through a 9x9 matrix based on cross-effects. Also, the results showed; Support drivers and organizational infrastructure, management factors, and content play an important role in improving system relationships, which are both influential and influenced. The drivers of strategic alignment of knowledge management and the environment of knowledge management had been the least influenced and the most influential, which is necessary to pay attention to these indicators according to the conditions of knowledge management in Tehran Municipal Sports Organization. Also, the drivers of knowledge management processes and flow, information technology infrastructure, and employees are more effected and less effective. The drivers of evaluation do not play a key and important role in the formation of the spatial organization of the maturity of knowledge management in the sports organization of Tehran Municipality. According to the identified drivers, it is necessary for the officials of Tehran Municipal Sports Organization to mature the knowledge management in this organization by emphasizing these factors.Extended abstractIntroductionKnowledge is a fluid mixture of experiences, new values, and new information, and it is embodied in organizations not only in documents and knowledge reserves, but also in the working procedures of organizational processes and norms (Makvandi et al, 2019). Inside the organization, this knowledge exists not only in the documents and databases of the organization, but also in all the activities, processes, actions and normes of the organization. Knowledge is divided into two types, implicit and explicit. Explicit knowledge is knowledge that is clearly written and coded in words, numbers, and figures; and can be accessed and stored in books, documents, plans, reports and documentaries (Alidoost Ghahfarokji et al, 2022).Therefore, organizations need flexibility in almost all aspects of their existence for their survival. On the other hand, preserving knowledge capitals and continuous use of them is also a reason for organizations to seek to use knowledge management and apply it more than before (Bayat et al, 2022). Through knowledge management, managers try to extract the knowledge accumulated in the minds of the members of the organization and share it among all people. In this case, the knowledge stored in the system becomes a permanent usable resource and provides a sustainable competitive advantage for the organization. (Dindar et al, 2022). Knowledge management is the process through which organizations use their collected information. Approaches to knowledge management depend on the management perspective; the differences can be caused by the information-based, technology-based, and culture-based perspectives (Asgharneghad & haghdoust, 2022). Therefore, the research begins with this question: how is the design of the driving force model affecting the maturity of knowledge management in the sports organization of Tehran Municipality?Theoretical FrameworkKnowledge managementKnowledge is one of the most important resources and funds to achieve this defensive advantage, so that knowledge management is considered as a key lever to improve performance, increase productivity and creativity, and facilitate innovation in organizational environments (Rossidis & Belias, 2020; Naeji, 2023). Knowledge management is a strategy that seeks to capture and organize knowledge, and tries to improve organizational capacities to compete and produce value. Therefore, we must know that knowledge management is not only about technology, but about processes, people, behaviors, and work flow. Thus, creating an organizational knowledge base should be recognized as a valuable resource (Rossidis & Belias, 2020).Shafaei et al, (2024) investigated the impact of knowledge management on organizational performance with regard to the mediating variable of business process management. The findings of the research showed that based on the significant values of the hypotheses, all three hypotheses were confirmed. The impact of knowledge management on business process management was 0.742; the impact of knowledge management on organizational performance was 0.422; and the impact of business process management on organizational performance was 0.652. Therefore, the most important proposal of the research is to pay attention to the preservation, sharing and application of knowledge, which is effective both in managing business processes and in increasing the level of organizational performance.Dindar et al, (2022) investigated the design of the knowledge management model in the Tehran Municipal Sports Organization. To analyze the data, three stages of open, central, and selective coding were used, which resulted in a total of 58 open codes, categorized in five categories of causal conditions (organizational culture, technological infrastructure, long-term investment, road map), contextual conditions (the support of top managers, the life cycle of the organization, expert manpower, and the dispersion of the organization's centers), intervening conditions (the role of governance, material and intellectual property rights, and competitors), strategies (empowerment of human resources, knowledge-orientation of organization, implementation of knowledge management strategy, reward system redesign, and structure redesign), and consequences (decision-making improvement, developing and creating new knowledge, increasing creativity and innovation, and identity building). Due to the fact that the atmosphere of the organization has changed from the traditional form to a knowledge-centered one, the sports organization of Tehran Municipality should adjust their knowledge management strategies while adapting to the changes. Research methodologyAccording to its purpose, the research method is applicable; qualitative in terms of implementation; and analytical and exploratory in nature. The statistical population includes 19 experts and faculty members of universities selected by the purposeful sampling method. Data collection was done using semi-structured interviews with members of the statistical community.Research findingsThe analysis of the data was done by the metacombination method, and MICMAC software was used. The data analysis showed that 32 key indicators and 9 sectors were identified through a 9x9 matrix based on cross-effects. Also, the results showed; Support drivers and organizational infrastructure, management factors, and content play an important role in improving system relationships, which are both influential and influenced. The drivers of strategic alignment of knowledge management and the environment of knowledge management had been the least influenced and the most influential, which is necessary to pay attention to these indicators according to the conditions of knowledge management in Tehran Municipal Sports Organization. Also, the drivers of knowledge management processes and flow, information technology infrastructure, and employees are more effected and less effective. The drivers of evaluation do not play a key and important role in the formation of the spatial organization of the maturity of knowledge management in the sports organization of Tehran Municipality. According to the identified drivers, it is necessary for the officials of Tehran Municipal Sports Organization to mature the knowledge management in this organization by emphasizing these factors.ConclusionThe current research was conducted with the aim of designing a model of drivers influencing the maturity of knowledge management in Tehran Municipal Sports Organization. The results of this research are in agreement with the results of Shafaei et al, (2024), Asgharneghad & Haghdoust (2022), Dindar et al, (2022), Jalali & Jafari (2022), Kiyani & Nazari (2021), Purrashidi (2021), Sarlak & Kasraei (2020), Khajepour et al, (2019), Payal et al, (2019), and Zaim et al, (2019). Dehghanpouri et al, (2020) showed that the maturity percentage of knowledge management in line with business strategies is 13.69%. The strategic, organizational-human, and technical-content dimensions have a significant impact on business. Therefore, in order to make purposeful the use of knowledge, and organize the stages and levels of its development, it is necessary to know the current situation in the field of knowledge management and determine the factors influencing decision-making, in order to apply and improve knowledge management in line with business.According to the results of this research, the following suggestions are presented: Considering that Tehran Municipal Sports Organization has the second level of maturity, in order to achieve a higher level, the level of ability of codes, financial and time resources, communication and knowledge flow, presenting the value of knowledge management and participation and involving people should be improved. Allocating sufficient resources to knowledge management activities, ensuring the availability of resources when investing in the field of knowledge management and providing sufficient time to employees will be appropriate measures to improve the maturity of financial and time resources to perform knowledge activities.